Hybrid scaffolding strategy for dermal tissue reconstruction: a bioactive glass/chitosan/silk fibroin composite. Issue 24 (17th February 2016) - Li, Danrong; Jiao, Genlong; Zhang, Wu; Chen, Xiaofeng; Ning, Ruijian; Du, Chang
Abstract : Regeneration of deep burn wounds is a very complex process that strongly relies on the tissue response between the dermal substitute and the newly-formed dermis. Abstract : Regeneration of deep burn wounds is a very complex process that strongly relies on the tissue response between the dermal substitute and the newly-formed dermis. In this research, we introduced a multifunctional integrated strategy for dermal tissue reconstruction. A porous BG/CHI/SF composite scaffold was prepared by freeze-drying a silk fibroin (SF) solution containing bioactive glass (BG) and chitosan (CHI). Fourier transform infrared (FTIR) spectroscopy, scanning electron microscopy (SEM) and thermogravimetry (TG) confirmed the chemical structure of the composite scaffold and its three-dimensional (3D) architecture. In vitro and in vivo investigations indicated that this composite scaffold presented excellent biocompatibility and tissue-repairing capability. Most importantly, a vascularisation evaluation demonstrated that the BG/CHI/SF composite scaffold possessed an outstanding ability to promote newly-formed and maturated blood vessels, which may accelerate the wound regeneration process. We therefore believe that this BG/CHI/SF multifunctional integrated scaffold has great potential in dermal tissue reconstruction.